2008
DOI: 10.1158/1535-7163.mct-07-2200
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of AKT1 enhances radiation toxicity of human tumor cells by inhibiting DNA-PKcs-dependent DNA double-strand break repair

Abstract: We have already reported that epidermal growth factor receptor/phosphatidylinositol 3-kinase/AKT signaling is an important pathway in regulating radiation sensitivity and DNA double-strand break (DNA-dsb) repair of human tumor cells. In the present study, we investigated the effect of AKT1 on DNA-dependent protein kinase catalytic subunit (DNA-PKcs) activity and DNA-dsb repair in irradiated non-small cell lung cancer cell lines A549 and H460. Treatment of cells with the specific AKT pathway inhibitor API-59CJ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
162
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 46 publications
(41 reference statements)
16
162
0
Order By: Relevance
“…We observed inhibition of Akt activity impaired the repair of radiation-induced DNA-DSB damage in CNE2 cells, whereas activated Akt promoted the repair of radiationinduced DNA-DSB damage in HeLa cells (Figure 1). These results were consistent with other recent studies which reported that activated Akt may decrease the efficacy of radiation therapy through promoting DNA repair in non-small-cell lung cancer cell lines and malignant-glioma cell lines (Tran et al, 2002;Kao et al, 2007;Toulany et al, 2008). Together, all these indicate that Akt can modulate radiation-induced DNA-DSB damage repair, and can regulate the efficacy of radiation therapy in other types of human cancers in which Akt kinase is hyperactivated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed inhibition of Akt activity impaired the repair of radiation-induced DNA-DSB damage in CNE2 cells, whereas activated Akt promoted the repair of radiationinduced DNA-DSB damage in HeLa cells (Figure 1). These results were consistent with other recent studies which reported that activated Akt may decrease the efficacy of radiation therapy through promoting DNA repair in non-small-cell lung cancer cell lines and malignant-glioma cell lines (Tran et al, 2002;Kao et al, 2007;Toulany et al, 2008). Together, all these indicate that Akt can modulate radiation-induced DNA-DSB damage repair, and can regulate the efficacy of radiation therapy in other types of human cancers in which Akt kinase is hyperactivated.…”
Section: Discussionsupporting
confidence: 93%
“…The number of g-H2AX correlates with the amount of unrepaired damage (Celeste et al, 2002;Aten et al, 2004;Kao et al, 2007), and a strong correlation between g-H2AX and cell death has been reported (Banath and Olive, 2003). Thus, g-H2AX foci assay has been regarded as a sensitive and specific assay for unrepaired DSBs (Taneja et al, 2004;Bao et al, 2006;Kao et al, 2007;Toulany et al, 2008). However, this also can lead to extra DSBs when the cells progress into S phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In tumor cells, however, which are usually more dependent on PI3K-mediated survival signaling and frequently express stimuli-independent activity of this signaling cascade (Yuan and Cantley, 2008), the relationship between PI3K and DNA-PK can be altered. Here, Akt has been reported to be an activator of DNA-PK, responsible for its phosphorylation (Toulany et al, 2006(Toulany et al, , 2008. These findings are consistent with our own data, which show that in doxorubicin-treated GBM cells, Akt is not downstream of DNA-PK, as inhibition of the latter does not affect phosphorylation of the former (Supplementary Figure 3d).…”
Section: Discussionsupporting
confidence: 92%
“…The latter protein is responsible for 'cleaning up' the DNA ends at break point, a process essential for repair initiation (Jackson, 2002). Furthermore, DNA-PK has been shown to be a co-activator of Akt (Bozulic et al, 2008), but the inverse relationship between these two kinases, with Akt being an activator of DNA-PK, has also been described (Toulany et al, 2008). This suggests that the PI3K/Akt pathway and DNA repair processes are intricately linked.…”
Section: Introductionmentioning
confidence: 99%